Effect of Reduced Plantar Sensation on Human Gaits on Various Terrains - Suzuki, Shinichiro; Chaki, Akira; Sekiguchi, Kentaro; Ding, Ming; Takemura, Hiroshi; Mizoguchi, Hiroshi (Journal of Robotics and Mechatronics, 2011)
The aim of this study is to investigate the effects of plantar tactile sensibility on the gaits of subjects walking on regular and irregular terrains. We took 3-dimensional measurements of gait motions with a method of ice immersion to reduce plantar sensation, and we compared it to the measurements under normal (not iced) conditions. The subjects were 8 healthy men (21.9±0.8 years old). In these experiments, the subjects immersed their feet in ice water for 30 minutes. We conducted the experiments on even terrain and uneven terrain (48 trials in total per subject). We also measured 6-axis plantar reaction forces of subjects while they were walking. The subjects were 5 healthy young men (22.6±0.5 years old), and there were 25 trials in total. As a result, the results of the gait velocity (p <0.07), step length (p <0.96), and step width (p <0.5) on even terrains did not change significantly after the ice immersion. By contrast, on uneven terrain with a gait of free velocity, the gait velocity (p <0.01) and the step length (p <0.01) significantly decreased after the ice immersion. On uneven terrain with a gait of maximum velocity, the step length (p <0.01) significantly decreased, and the step width variability (p <0.03) increased after the ice immersion. Force variability in the back-to-front direction (p <0.03) and moment variability in pitch axis (p <0.004) significantly decreased, and roll axis moment variability (p <0.05) significantly increased after the ice immersion. These results support the hypothesis that reduced plantar sensation has a significant effect on human gaits, especially when a person is walking on uneven terrain.